PARTICIPATING ENGLISH COURSE; DOES IT HAVE ANY EFFECT TOWARD STUDENTS’ SPEAKING PERFORMANCE IN SCHOOL? - Amelia, Yuni (Paedagogia: Jurnal Pendidikan, 2016)
The purpose of this study was to find out the effects of participating English school toward Eighth Grade Students’ speaking performance at SMPN 3 Palu. This research used descriptive research. This research used purposive sampling in selecting the students as the sample. There were fifthteen selected students who participated in English school and fifthteen other students who did not participate in English school. The data collection was done through interview and test. Interview was conducted to the English teacher and students who participated in English school. Speaking test was given to students who participated and did not participate in English school.The researcher analyzed the result of interview descriptively. The mean score from students’ speaking test showed a difference. The students who did not participate English school got 52.30 and the students who participated in English school got 60,66. The students who participated in English school got higher score than the students who did not participate in English school. Based on the result of interview and speaking test, it can be concluded that the students get positive effects during they participate in English school. Participating in English school could help the students to have better speaking performance at the school.